2010
DOI: 10.1002/jmor.10883
|View full text |Cite
|
Sign up to set email alerts
|

The pelvic kidney of male Ambystoma maculatum (Amphibia, urodela, ambystomatidae) with special reference to the sexual collecting ducts

Abstract: This study details the gross and microscopic anatomy of the pelvic kidney in male Ambystoma maculatum. The nephron of male Ambystoma maculatum is divided into six distinct regions leading sequentially away from a renal corpuscle: (1) neck segment, which communicates with the coelomic cavity via a ventrally positioned pleuroperitoneal funnel, (2) proximal tubule, (3) intermediate segment, (4) distal tubule, (5) collecting tubule, and (6) collecting duct. The proximal tubule is divided into a vacuolated proximal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

10
49
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6

Relationship

6
0

Authors

Journals

citations
Cited by 18 publications
(59 citation statements)
references
References 25 publications
10
49
0
Order By: Relevance
“…With light microscopy, Spengel (1876) noted that nephron structure (regionality) was identical between the two kidney regions and thus hypothesized that nephrons from the pelvic and genital kidneys were both involved in urine formation, with the added function of sperm transport in genital kidney nephrons. Siegel et al (2010Siegel et al ( , 2013 and Nicholson and Siegel (2014) confirmed Spengel's hypothesis that regionality of nephrons in the genital and pelvic kidneys was identical but also provided evidence with the use of transmission electron microscopy that genital kidney proximal and distal tubules were modified from those of pelvic kidney proximal and distal tubules for sperm transport. These modifications included ciliated proximal tubule epithelial cells in the genital kidney and reduced basal plasma membrane folding of the epithelia in both genital kidney proximal and distal tubules in Ambystoma maculatum and Notophthalmus viridescens.…”
supporting
confidence: 66%
See 2 more Smart Citations
“…With light microscopy, Spengel (1876) noted that nephron structure (regionality) was identical between the two kidney regions and thus hypothesized that nephrons from the pelvic and genital kidneys were both involved in urine formation, with the added function of sperm transport in genital kidney nephrons. Siegel et al (2010Siegel et al ( , 2013 and Nicholson and Siegel (2014) confirmed Spengel's hypothesis that regionality of nephrons in the genital and pelvic kidneys was identical but also provided evidence with the use of transmission electron microscopy that genital kidney proximal and distal tubules were modified from those of pelvic kidney proximal and distal tubules for sperm transport. These modifications included ciliated proximal tubule epithelial cells in the genital kidney and reduced basal plasma membrane folding of the epithelia in both genital kidney proximal and distal tubules in Ambystoma maculatum and Notophthalmus viridescens.…”
supporting
confidence: 66%
“…All other studies with light microscopy provided the same results; i.e., all salamanders possess both pelvic and genital kidney nephrons and the same nephron regions can easily be identified in the pelvic and genital kidneys; i.e., renal corpuscles with glomeruli (although evidence of reduction was observed in Plethodontidae), proximal tubules, distal tubules, and collecting tubules (Siegel et al, 2010(Siegel et al, , 2012b(Siegel et al, , 2013(Siegel et al, , 2014aNicholson and Siegel, 2014).…”
mentioning
confidence: 53%
See 1 more Smart Citation
“…A SSK also occurs as a secondary sexual structure in male Gasterosteidae (stickleback fish : Courrier, 1922;Jakobsson et al, 1999), in which the secretion is involved in construction of foam nests, and some male Caudata (salamanders: Siegel et al, 2010), in which the function of the secretion is unknown. The modified portions of the kidney tubules are considered to be independently evolved in squamates, fish, and salamanders (Siegel et al, 2010).…”
mentioning
confidence: 99%
“…Within stickleback fishes, it is found within the ventral kidney (Courrier, 1922), and within salamanders, it is restricted to the collecting ducts (Siegel et al, 2010). Within the Squamata, the location of the SSK can include the intermediate segment, distal convoluted tubule (DCT), collecting duct, ureter (Ur), and combinations of the aforementioned (for review, see Rheubert et al, 2011).…”
mentioning
confidence: 99%